THE PROBLEM OF USING DIFFERENTIATED TASKS IN FOREIGN LANGUAGE LESSONS AS A MEANS IMPROVING THE QUALITY OF STUDENTS' KNOWLEDGE (Pedagogy of Higher and Secondary Education, 2006)
The article studies the problems of using various tasks at foreign languages lessons.